A field programmable gate array controlled high‐current pulsed source for airborne transient electromagnetic system. Issue 7 (6th April 2021) - Liu, Wei; Hu, Xuquan; Liao, Xian; Liu, Longhuan; Fu, Zhihong
Abstract: A high‐current pulsed source with high charging efficiency, high stability and low current ripple is proposed for airborne transient electromagnetic method application. The high voltage capacitor bank is employed to provide and store energy for generating current pulses in the inductive load. An N‐channel interleaved boost module is designed to replenish the capacitor energy gap so that current pulses can be repeated in a short time. The operation principles of the proposed topology are explained and the theoretical analysis is provided. In addition, a convenient and effective control strategy to raise efficiency of the charging circuit is introduced. The concise closed‐loop control method directed at the characteristics of load variations is available for changing the steady operation and control the output current. Logic input and output modules based on field programmable gate array are designed for the controller. A laboratory prototype with the maximum peak current 400 A is built for the load coil of 2.1 mH and 150 mΩ to verify the effectiveness of the proposed topology and control method.